2021
DOI: 10.25046/aj060261
|View full text |Cite
|
Sign up to set email alerts
|

Complex Order PIa+jbDc+jd Controller Design for a Fractional Order DC Motor System

Abstract: Fractional order controller DC motor Complex order controller Bode diagram Root locus Industry 4.0 implementation stipulates effective actuator control. In the present work, a complex order PI a+ jb D c+ jd (COPID) controller was designed for a fractional order model of a direct current (DC) motor system. For comparisons, the DC motor system model was also controlled using the conventional proportional integral (PI), proportional integral derivative (PID), proportional resonant (PR) and fractional order PID co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 43 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…30 As discussed earlier, the CO-PID control procedure has been proposed in the available literature for DC motor’s speed control, inverted pendulum’s balancing control, and surface roughness control in machining applications. 21,22,31 However, the dynamics of the glucose-insulin interactions in human body are quite different than that of the aforementioned electro-mechanical systems. The CO-PID controller, formulated in this section, introduces additional controller parameters that increases the controller’s degrees of freedom and improves its design flexibility, which enables it to effectively track the reference under exogenous disturbances.…”
Section: Proposed Complex Order Pid Control Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…30 As discussed earlier, the CO-PID control procedure has been proposed in the available literature for DC motor’s speed control, inverted pendulum’s balancing control, and surface roughness control in machining applications. 21,22,31 However, the dynamics of the glucose-insulin interactions in human body are quite different than that of the aforementioned electro-mechanical systems. The CO-PID controller, formulated in this section, introduces additional controller parameters that increases the controller’s degrees of freedom and improves its design flexibility, which enables it to effectively track the reference under exogenous disturbances.…”
Section: Proposed Complex Order Pid Control Methodologymentioning
confidence: 99%
“…20 The studies have shown that the assignment of complex orders to the aforementioned operators increases the controller’s degrees of freedom, which enhances its resilience against parametric uncertainties especially when the gain and phase characteristics are notable. 21 The complex-order controllers are extensively used to solve practical control engineering problems owing to their aforementioned attributes. 22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive investigations have been carried out to incorporate automated architectures in diverse fields such as bolted joints [1], lean manufacturing [2], bio-fuelled engines [3], flexible robotic arms [4], Covid therapy robots [5], industrial DC motors [6], machining of exotic materials [7]- [18], ball nose end milling [19] and many more [20]- [34]. Many of these investigations included applications of various heuristic algorithms to attain optimal solutions to the automation/control problems [35]- [46]. The following subsections give details of some of the latest literature reviews and bibliometric research investigations in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Time domain, frequency domain and stability analysis of linear systems represented by differential equations with complex order derivative has been carried out [9]. It has found applications such as the design of controller for fractionalorder DC motor system [10], in PID controller and low-pass filter [11]. Such systems have been found to have large stability regions for certain parameters.…”
Section: Introductionmentioning
confidence: 99%